TERAPI MELUKIS TERHADAP KOGNITIF PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA SAMBANG LIHUM - Norsyehan; Lestari, Dhian Ririn; Mulyani, Yeni (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Painting therapy is a therapy which encourages someone to express and to understand the emotiontrough artistic expressions and creative process to be able to cure cognitive, affective, andpsychomotoric functions. This study was aimed to find the effect of painting therapy on theschizophrenia patients’ cognitive. This study used pre-experiment method with design approach onegroup pre and post design. The respondents involved in this study were 30 patients with accidentalsampling. The data collection was done using cognitive ability measurement before and after thepainting therapy. The experiment analysis used T- test dependent. The result of the study showed thatthere was an effect of painting therapy treatment on the schizophrenia patients’ cognitive at SambangLihum psyichiatric hospital with the significant value of 0.000 which meant p< 0.05. It was suggestedto apply painting therapy on schizophrenia patients to improve their cognitive function.